Analisis litter size, bobot lahir dan bobot sapih hasil perkawinan kawin alami dan inseminasi buatan kambing Boer dan Peranakan Etawah (PE) - Kaunang, Dedy; Suyadi, S.; Wahjuningsih, Sri (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
ABSTRACT:  The quality of semen inseminated to the dam might influence on the fer-tilization process and fetal growth during pregnancy. The aim of this research was to analysis the litter size, birth and weaning weight of Boer x PE goat crosses. Forty one parous and multiparous Peranakan Etawah (PE) does were naturally mated with selected Boer buck (NM-group), while the other 24 does were inseminated using artificial tech-nique using semen collected from the same buck as NM-group  and called as AI-group. The result showed no significant differences in litter size, birth weight and weaning weight between kids resulting from the does mated naturally and artificially insemina-tion technique (1.8±0.64 vs. 1.79±0.58; 2.93±0.568 vs. 2.96±0.397 kg; and 11.06 ± 2.001 kg vs. 11.31 ± 1.54 kg, for litter size, birth weight and weaning weight, respec-tively. It was concluded that mating technique in cross mating between PE does x Boer buck did not influence on the litter size and early growth phase of kids. Keywords: PE does, Boer buck, natural mating, artificial insemination